Kajian Sosial-Semiotik Estetika Dongeng dalam Visualisasi Musik Video Blue Hour oleh TXT - Sutanto, Shienny; Sutanto, Shienny Megawati; Wardaya, Marina (Visualita Jurnal Online Desain Komunikasi Visual, 2026)
The K-pop industry utilizes music videos (MVs) not only as promotional media but also as multimodal communication platforms that integrate lyrics, visuals, and music to construct narratives and emotional engagement with global audiences. Blue Hour by TXT (Tomorrow X Together) stands out for its use of the blue hour phenomenon as a conceptual foundation that represents a liminal, magical, and temporary experience of transition. This study aims to analyze how meaning is constructed through multimodal interaction in the Blue Hour MV, and how such meaning is organized through representational, interactive, and compositional meanings. This research employs a qualitative interpretative approach with multimodal analysis as its main framework. The findings show that meaning emerges through the integration of modes. Lyrics provide semantic direction, visuals expand it through color, space, and symbols, while music regulates rhythm and emotional intensity. This study confirms that the Blue Hour MV is a complex multimodal construction and demonstrates the potential of natural phenomena as visual concepts in designing coherent, emotional, and meaningful storytelling within digital visual culture.